Improved performance of colloidal quantum dot solar cells using high-electric-dipole self-assembled layers. (September 2017) - Azmi, Randi; Nam, So Youn; Sinaga, Septy; Oh, Seung-Hwan; Ahn, Tae Kyu; Yoon, Sung Cheol; Jung, In Hwan; Jang, Sung-Yeon
Abstract: High performance colloidal quantum dot (CQD) solar cells were developed by modifying ZnO electron accepting layers (EALs) using self-assembled monolayers (SAMs) of highly polar molecules. A high molecular dipole moment of −10.07D was achieved by conjugating a strong electron donor, julolidine, to an electron acceptor, a cyanoacetic acid unit, through a thiophene moiety. The energetic properties of ZnO EALs were manipulated with respect to the dipole moment of the modifying molecules. The built-in potential ( V bi ) and internal electric field ( E int ) of CQD solar cells could thereby be tuned. The power conversion efficiency (PCE) of the SAM modified devices was improved from 3.7% to 12.9% relative to the unmodified devices as a function of molecular dipole moments (from −5.13D to −10.07D). All figures-of-merit of solar cells were improved simultaneously by SAM modification due to enhanced V bi, E int, and charge collection efficiency. The PCE of the highly polar molecule modified devices reached 10.89% with a V OC of 0.689 V, whereas that of the unmodified devices was 9.65% with a V OC of 0.659 V. Notably, the remarkably low energy loss of 0.433 eV is achieved in the SAM modified devices. Graphical abstract: High efficiency colloidal quantum dot solar cells were developed using highly polar SAM modified ZnO electron accepting layers. The solar cell performance was improved by the modification due to enhanced internal electric field and charge collection efficiency. The power conversion efficiency of 10.89% with energy loss of 0.433 eV was achieved. Highlights: High efficiency colloidal quantum dot solar cells were developed using highly polar SAM modified ZnO electron accepting layers. Synthesized novel self-assembling highly polar molecules for electric dipole layer (EDL). The solar cell performance was improved by the modification due to enhanced internal electric field and charge collection efficiency. The power conversion efficiency of 10.89% with energy loss of 0.433 eV was achieved.